(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The purpose of this research article was to determine the relationship between Solid Waste Management and Sustainable Development in a municipality of Lima, Peru in the context of COVID-19. The methodology was quantitative approach, correlational level, cross-sectional and non-experimental design. The population was made up of a total of 274 workers, while through probability sampling a total of 161 workers were obtained. It was used as the survey technique for each study variable, obtaining a reliability of 0.918 for the Solid Waste Management instrument and of 0.663 for Sustainable Development. To measure the correlation between the variables, the Spearman Rho Coefficient was used using the Statistical Package of Social Sciences (SPSS) version 24. Among the results, it was obtained that the Spearman Rho correlation coefficient is weak and significant (r = 0.469, p = 0.000), while for the solid waste management dimension a moderate and significant correlation was obtained (r = 0.626, p = 0.000); Finally, for the solid waste management dimension, a weak correlation was obtained and without significance (r=0.135, p = 0.088). In conclusion, a better level of solid waste management will be reflected in a better level of sustainable development in the municipality under study.